Scorpion alleviates bone cancer pain through inhibition of bone destruction and glia activation. (March 2020) - Yu, Jiachuan; Luo, Yuanyuan; Jin, Huidan; Lv, Jiaxin; Zhou, Tingting; Yabasin, Iddrisu Baba; Wen, Qingping
Background: Bone cancer pain is common in patients with advanced cancers as tumor metastasizes to bone. The inefficient clinical treatment severely reduces quality of life of bone cancer pain patients. During the pain status, activated spinal astrocytes and microglia release various inflammatory cytokines, resulting in spinal inflammation and the development of neuron sensitization. Scorpion is the dry body of Buthus martensii Karsch and is often used for various pain management in clinical practice. However, its function on bone cancer pain is unclear. Methods: We investigated the effects of intragastric administration of scorpion on bone cancer pain induced by left tibial cavity injection of Walker 256 cells. Nociceptive behavior was measured using the von Frey filaments test and the spontaneous ambulatory pain score. The bone destruction was assessed by tibial radiographs. Expression of spinal cord astrocyte marker glial fibrillary acidic protein and microglial marker Iba1 was monitored by Western blot assay and immunofluorescence. Tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6, and IL-1β was detected by real-time polymerase chain reaction. The proliferation of Walker 256 cells was evaluated by CCK8 assay. Results: Intragastric administration of scorpion reduced bone cancer pain behavior and relieved bone destruction, accompanied by decreased expression of spinal glial fibrillary acidic protein and Iba1 protein level and TNF-α, IL-6, and IL-1β mRNA level. Besides, scorpion inhibited proliferation of Walker 256 cells in a dose- and time-dependent manner. Conclusion: Our results demonstrate that scorpion produces an analgesic effect in a rat model of bone cancer pain via inhibiting bone destruction and activation of spinal cord astrocytes and microglia.